Curriculum Development Design of Elementary-Based Islamic Boarding School - Fitriyah Mahdali; Sita Acetylena; Muhammad Husni (AL-ISHLAH: Jurnal Pendidikan, 2022)
The applied curriculum is still using the elementary school curriculum in general, which does not adopt the values of Islamic Boarding School. Based on logic of the PAR (Participatory Action Research) approach as well as the results of FGD (Focus Group Discussion) and SWOT analysis, the carried out service treatments are mentoring and development of Islamic boarding school-based elementary school curriculum design. This mentoring was given to the curriculum development team of SDI Turen Malang by bringing in a third party who is the head of the curriculum at the Islamic boarding school. In addition to a facilitator, researcher as graduate from Islamic Boarding School who was part of the curriculum development team of Islamic Boarding School also provided direction and contributed concepts. In this curriculum, the basis of innovation is the introduction of Islamic religious teachings by integrating the curriculum. The curriculum development model of Islamic Boarding School for SDI Turen into an Islamic Boarding School-based curriculum in this service is emphasized on 4 points, namely: 1) Integration of religious values in the learning process, 2) Addition of religious subjects, 3) Use of the yellow book as a reference, and 4) Habituation of religious activities. The hope is that SDI Turen can use this curriculum development design into a permanent school curriculum as an effort to realize the dream of becoming an Islamic Boarding School-Based School.